Correlational Study on the Contextual Factors Influencing the Effectiveness of Flexible Learning: the Case of One State University in the Philippines - Alberto D. Yazon; Mario R. Briones; Eden C. Callo (International Journal of Management, Entrepreneurship, Social Science and Humanities, 2021)
With the onset of the pandemic, no face-to-face instruction is seemingly the most pressing problem faced today in schools. The acquisition of required skills has been challenged by the digital divide and limited access to quality and equitable higher education. This scenario has pushed LSPU for further flexibility in rendering its services anchored on its vision of becoming a center of technological innovation that promotes interdisciplinary learning, sustainable utilization of resources, collaboration, and partnership with the community and stakeholders. Hence, this quantitative, non-experimental research with observational approach utilized predictive design explored the LSPU's delivery and assessment of flexible learning based on the outcomes-based education. The research instrument with an excellent reliability coefficient of .962. was programmed in the google form and the extracted data from 5,314 respondents were analyzed using summary statistics and regression analysis. Multiple linear regression analysis was used to treat the data. It was found out that there is a high extent of implementation of sound assessment practices that support student learning. The respondents agreed that the level of teacher’s assessment practices and support to student learning are promising and attuned to the requirements of flexible learning. The University’s migration plan really worked for the faculty and students. Majority of the respondents are motivated and engaged in flexible learning. The study found that 55.1% variance in the effectiveness of the implementation of flexible learning is positively explained by teacher’s assessment practices and support to students, student’s attainment of cognitive learning outcomes, student’s engagement and motivation, and student’s self-assessed academic performance during the new normal.